A process for the complex insulation treatment of carbonyl iron powder
By forming a composite insulation process of phosphate conversion film and silica coating layer on the surface of carbonyl iron powder, the problems of limited improvement in insulation resistance and insufficient film density in the prior art are solved, and a balance between high insulation performance and magnetic properties is achieved, which is suitable for high frequency and high current inductor devices.
Patent Information
- Application Number
- CN202611154315.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-11-06
AI Technical Summary
In existing technologies, the phosphating treatment of carbonyl iron powder has a limited effect on improving insulation resistance, while single silica coating faces insufficient film density and continuity, making it difficult to meet the comprehensive requirements of high insulation resistance, high density and high weather resistance stability of the insulation layer in high frequency and high current scenarios.
A composite insulation process is adopted, in which phosphoric acid is dissolved and mixed with organic solvent and then baked to form a phosphate conversion film. Then, a silica coating layer is formed on the surface of the phosphate conversion film using sodium silicate solution and hydrochloric acid solution, forming a double-layer composite insulation structure to ensure the continuity and density of the insulation layer.
It significantly improves the surface insulation resistance and dielectric breakdown voltage of the particles, reduces the core eddy current loss over a wide frequency range, and enhances the powder's resistance to high temperature and high humidity aging. At the same time, it maintains the stability of high saturation magnetic induction intensity and wide frequency permeability, making it suitable for the low loss requirements of high-frequency high-current inductive devices.
Abstract
Description
Technical Field
[0001] This invention relates to the field of carbonyl iron powder technology, specifically to a composite insulation treatment process for carbonyl iron powder. Background Technology
[0002] Carbonyl iron powder is a high-purity spherical iron powder prepared by the thermal decomposition of pentacarbonyl iron. Among soft magnetic powder materials, it has the highest saturation magnetic induction intensity and relatively stable permeability in a wide frequency range of 1kHz to 100MHz. Therefore, it is widely used in inductor devices such as integrally molded inductors and magnetic ring inductors, which have high requirements for high current carrying capacity and high frequency stability.
[0003] Soft magnetic powder materials generate magnetic losses when operating in an alternating magnetic field. These losses mainly consist of three parts: hysteresis loss, eddy current loss, and residual loss. Hysteresis loss and residual loss are primarily determined by the type of powder material, its crystal structure, and internal defects, leaving relatively limited room for improvement. Eddy current loss, however, is mainly determined by the particle size and the insulation resistance of the insulating layer on the particle surface. Under the condition that the particle size and operating frequency are the same, the higher the insulation resistance of the insulating layer on the particle surface, the more thoroughly the eddy current loops between particles are broken, resulting in lower eddy current loss. Therefore, improving the insulation resistance of the insulating layer on the surface of carbonyl iron powder particles is one of the key technical paths to reduce the loss of magnetic components and improve device efficiency under high-frequency conditions.
[0004] In industry practice, improving the surface insulation resistance of carbonyl iron powder particles mainly relies on powder manufacturers building an insulating layer on the surface of the raw powder, while downstream inductor manufacturers usually supplement the insulation by using adhesives such as epoxy resin during the pressing and molding process.
[0005] In existing technologies, there are two common technical approaches to surface insulation treatment of carbonyl iron powder or similar soft magnetic metal powders:
[0006] One approach is phosphating, which involves reacting phosphoric acid or phosphate solution with the surface of iron-based powder to form a phosphate conversion film as an insulating layer. This approach is relatively mature and cost-effective, but the phosphate conversion film formed by phosphating alone usually has inherent defects such as a thin film layer, localized micropores, or incomplete coverage. The improvement in insulation resistance and long-term stability (especially resistance to damp heat aging) are relatively limited.
[0007] The second route is silica coating, which uses silicon-containing compounds such as sodium silicate as raw materials to deposit silica (or its precursor silica gel) coating layer on the surface of iron-based powder particles through acidification and hydrolysis. If carbonyl iron powder without surface pretreatment is directly coated with silica, the distribution of naturally occurring active sites on the surface of carbonyl iron powder particles is uneven (e.g., differences in surface oxidation degree, micro-roughness, and local charge density between particles and within the particle surface). During the deposition and condensation of the film, silica colloid is prone to local enrichment and stacking in areas with dense active sites, while in areas with sparse active sites, there may be insufficient coverage or even exposure defects. Ultimately, it is difficult to form a dense and continuous silica coating layer on the particle surface.
[0008] It is evident that the existing technologies of phosphating and silica coating each have their limitations: phosphating has a limited improvement in insulation resistance, while silica coating alone faces the problem of insufficient film density and continuity. If either is used in isolation, it is difficult to fully meet the comprehensive requirements of carbonyl iron powder for high insulation resistance, high density, and high weather resistance stability of the insulation layer in high-frequency and high-current scenarios.
[0009] To overcome the above-mentioned defects, a composite insulation treatment process for carbonyl iron powder is proposed to solve the existing problems. Summary of the Invention
[0010] To address the shortcomings of existing technologies, this invention provides a composite insulation treatment process for carbonyl iron powder, which solves the problems of limited improvement in insulation resistance after phosphating carbonyl iron powder and insufficient film density and continuity when using single silica coating.
[0011] To achieve the above objectives, the present invention provides the following technical solution: a composite insulation treatment process for carbonyl iron powder, comprising the following steps:
[0012] Step 1, passivation treatment: Dissolve phosphoric acid in an organic solvent. The weight of phosphoric acid is 0.3% to 1.0% of the weight of the carbonyl iron powder. Add the carbonyl iron powder and stir to mix evenly. Then bake the mixture to form a phosphate conversion film on the surface of the carbonyl iron powder, thus obtaining the passivated carbonyl iron powder.
[0013] Step 2, silica coating: Dissolve sodium silicate in water to prepare a sodium silicate solution with a mass percentage of 6% to 10%, add the passivated carbonyl iron powder obtained in Step 1 and stir evenly to obtain part A;
[0014] Concentrated hydrochloric acid was dissolved in water to prepare a hydrochloric acid solution with an HCl concentration of 7% to 11%, thus obtaining part B;
[0015] Under the stirring conditions of part A, part B is added to part A at a uniform rate. Under the preset reaction conditions, the silica colloid formed by the hydrolysis and condensation of sodium silicate is deposited and coated on the surface of carbonyl iron powder particles with phosphate conversion film to form a silica coating layer. Then, it is filtered and washed with water.
[0016] Step 3, Dehydration and Drying: The product obtained in Step 2 is dried and dehydrated under an inert atmosphere;
[0017] Step 4: Crushing and sieving: The dried material obtained in Step 3 is crushed, batched, and sieved to obtain carbonyl iron powder with a double-layer composite insulating structure with a phosphate conversion film layer and a silica coating layer on the surface.
[0018] Preferably, the organic solvent in step one is acetone, and the baking temperature in step one is 80℃~150℃.
[0019] Preferably, the sodium silicate in step two is sodium silicate pentahydrate or sodium silicate nonahydrate; the mass of the solvent water in the sodium silicate solution is 20% to 30% of the mass of the carbonyl iron powder after passivation treatment.
[0020] Preferably, in step two, the mass of the water solvent in the hydrochloric acid solution is 4% to 6% of the mass of the carbonyl iron powder after passivation treatment, and the concentrated hydrochloric acid is analytical grade concentrated hydrochloric acid with an HCl mass concentration of 37%.
[0021] Preferably, in step two, the time for uniformly adding part B to part A is 30 to 120 minutes, the preset reaction conditions are pH controlled between 7 and 8.5, and stirring is continued for 20 to 40 minutes after the addition is completed.
[0022] Preferably, the inert atmosphere in step three is a nitrogen atmosphere, and the drying temperature is 80℃~120℃.
[0023] Preferably, the particle size D50 of the carbonyl iron powder product obtained in step four is 3μm to 50μm.
[0024] Preferably, the product after filtration in step two is washed with deionized water three or more times to remove residual soluble salts on the surface.
[0025] Beneficial effects
[0026] This invention provides a composite insulation treatment process for carbonyl iron powder. Compared with existing technologies, it has the following advantages:
[0027] (1) The composite insulation process of carbonyl iron powder, by setting a phosphating passivation layer as a uniform nucleation substrate of silicon dioxide, homogenizes the original uneven active sites on the surface of carbonyl iron powder particles, avoids the defects of local enrichment and stacking of silica colloid and local particle exposure, so that the outer silicon dioxide coating layer is continuous, dense and uniform in thickness, completely cuts off the conductive eddy current loop between particles, significantly improves the insulation resistance and dielectric breakdown voltage of particle surface, effectively reduces the eddy current loss of magnetic core in a wide frequency range, and is suitable for the low loss use requirements of high frequency high current inductor devices.
[0028] (2) The composite insulation treatment process of the carbonyl iron powder is to set up a double-layer series insulation structure of "phosphate passivation film and silicon dioxide coating layer". The inner phosphate film has basic insulation barrier capability and forms a composite insulation medium with the outer high insulation silicon dioxide layer. Compared with the single-layer phosphate film, the insulation performance is improved more. At the same time, the double film layers work together to form a double anti-corrosion barrier inside and outside. The inner passivation film isolates the iron substrate and the outer silicon dioxide blocks water vapor and corrosive media, which greatly improves the powder's resistance to high temperature and high humidity aging. The insulation performance decays slowly during long-term service, ensuring the long-term working stability of inductor devices under harsh conditions.
[0029] (3) The composite insulation treatment process of carbonyl iron powder, by setting phosphating pre-homogenization to regulate the silica deposition morphology, avoids excessive local accumulation of silica that squeezes out the effective magnetic phase ratio of the powder. While achieving high insulation performance, it retains the core magnetic characteristics of carbonyl iron powder, such as high saturation magnetic induction intensity and stable broadband permeability, to the greatest extent. This solves the performance contradiction of "insulation improvement leads to a significant decrease in permeability" in traditional single insulation processes, and achieves a two-way balance between insulation performance and magnetic properties.
[0030] (4) The composite insulation treatment process of carbonyl iron powder uses conventional raw material system of phosphoric acid organic phase phosphating and sodium silicate liquid phase hydrolysis coating. It adopts bulk low-cost industrial raw materials throughout the process, without the need for expensive special modification reagents. The whole process can be modified and implemented based on the existing mature powder surface treatment production line. The process parameter control window is wide, the reaction process is controllable, and the powder performance consistency between batches is high. It has the industrialization advantages of low cost and easy large-scale continuous production. Detailed Implementation
[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below.
[0032] A composite insulation treatment process for carbonyl iron powder includes the following steps:
[0033] Phosphating and passivation process: The amount of phosphoric acid added is 0.3% to 1.0% of the mass of carbonyl iron powder. Acetone is used as the organic solvent to dissolve the phosphoric acid. The solid-liquid mass ratio of the phosphating solution to the carbonyl iron powder is fixed at 1:4.
[0034] Operation process: Phosphoric acid is completely dissolved in acetone to obtain phosphating solution, carbonyl iron powder is added, and the mixture is stirred continuously at room temperature for 30 minutes to ensure complete dispersion of the powder. The mixture is then transferred to an oven for constant temperature baking for 2 hours. The baking temperature can be adjusted within the range of 80℃ to 150℃. After baking, the mixture is naturally cooled to room temperature to obtain passivated carbonyl iron powder with a phosphate conversion film formed on the surface.
[0035] Silica coating process: Sodium silicate pentahydrate is selected as the silicon source as the basic raw material. The mechanical stirring speed is kept constant at 400 r / min throughout the process. Complete operating parameter range: Sodium silicate slurry preparation: The amount of deionized water added is 20% to 30% of the mass of carbonyl iron powder after passivation. Sodium silicate pentahydrate is dissolved to prepare a sodium silicate solution with a mass fraction of 6% to 10%. The passivated iron powder is added and stirred continuously to form slurry A.
[0036] Preparation of hydrochloric acid acidification solution: Add deionized water at a rate of 4% to 6% of the mass of the passivated carbonyl iron powder, dilute with 37% analytical grade concentrated hydrochloric acid, and prepare hydrochloric acid solution B with a mass fraction of 7% to 11%.
[0037] Hydrolysis deposition reaction: Hydrochloric acid solution B is added dropwise to slurry A at a uniform rate. The total addition time is controlled between 30 and 120 minutes. The pH of the system is monitored in real time throughout the process. The dropping rate is adjusted to stabilize the pH at the reaction endpoint between 7 and 8.5. After all the acidified solution is added, the mixture is stirred continuously at room temperature for 20 to 40 minutes to ensure that the silica colloid is fully hydrolyzed and condensed and coated on the particle surface.
[0038] Solid-liquid separation and washing: After the reaction is completed, vacuum filtration is used to obtain a powder filter cake. The powder is washed more than 3 times with deionized water at 5 times the weight of iron powder until the conductivity of the filtrate is <50μS / cm to remove residual soluble sodium salt impurities on the surface of the powder.
[0039] Inert atmosphere dehydration and drying process: The powder filter cake after washing is placed in an oven protected by nitrogen. The nitrogen flow rate is constant at 0.5L / min. The drying temperature can be adjusted within the range of 80℃~120℃. The powder is dried at a constant temperature for 4 hours to completely remove the free moisture inside the powder and prevent the carbonyl iron powder from oxidizing in an oxygen-rich high-temperature environment.
[0040] Crushing, grading and sieving process: All operating parameters are fixed with no adjustment range: The dried agglomerated powder is lightly dispersed by an air jet mill, then transferred to a three-dimensional mixer for batch mixing for 30 minutes, and then passed through a 200-mesh standard sieve. The final carbonyl iron powder particle size D50 is controlled within the range of 3μm to 50μm.
[0041] Example 1 (Parameters for each process are taken as the lower limit of the range)
[0042] A composite insulation treatment process for carbonyl iron powder includes the following steps:
[0043] Phosphating and passivation treatment: Take carbonyl iron powder raw powder, add 0.3% of phosphoric acid by mass of raw powder, dissolve phosphoric acid in acetone to prepare phosphating solution, the solid-liquid mass ratio of phosphating solution to iron powder is 1:4, stir at room temperature for 30 minutes to completely disperse the powder, place the mixture in an oven at 90℃ for 2 hours, and after baking, cool naturally to room temperature to obtain passivated carbonyl iron powder with a thin phosphate conversion film on the surface;
[0044] Silica coating treatment: The stirring speed was kept constant at 400 r / min throughout the process;
[0045] Sodium silicate slurry preparation: Take 20% of the mass of passivated iron powder in deionized water, dissolve sodium silicate pentahydrate to prepare a sodium silicate solution with a mass fraction of 6%, add the passivated iron powder and stir continuously to obtain slurry A;
[0046] Preparation of hydrochloric acid acidification solution: Take 4% of the mass of passivated iron powder with deionized water, dilute with 37% concentrated hydrochloric acid, and prepare a 7.5% hydrochloric acid solution B.
[0047] Hydrolysis deposition reaction: Hydrochloric acid solution B is added dropwise to slurry A at a uniform rate for a total dropping time of 60 min; the dropping rate is adjusted in real time to control the pH at the reaction endpoint to 7.5; after the dropping is completed, the mixture is stirred at room temperature for 30 min to form a silica coating layer by uniformly depositing silica colloid on the surface of the phosphate film.
[0048] Solid-liquid separation and washing: The slurry is vacuum filtered to obtain a filter cake, which is then washed three times with 5 times the weight of deionized water (based on the iron powder) until the conductivity of the filtrate is <50μS / cm, thus removing soluble salt impurities.
[0049] Inert atmosphere dehydration and drying: The water-washed filter cake is placed in a nitrogen-protected drying oven with a nitrogen flow rate of 0.5 L / min and a drying temperature of 100℃ for 4 hours to fully remove the free moisture from the powder.
[0050] Crushing, grading and sieving: The dried agglomerated powder is lightly dispersed by an air jet mill, batched in a three-dimensional mixer for 30 minutes, and then passed through a 200-mesh standard sieve to obtain the finished product of double-layer composite insulating carbonyl iron powder with D50=7.8μm;
[0051] Example 2 (The parameters for each process are taken as the midpoint of the range; preferred example)
[0052] A composite insulation treatment process for carbonyl iron powder includes the following steps:
[0053] Phosphating and passivation treatment: Take carbonyl iron powder raw powder, add 0.5% of phosphoric acid by mass of raw powder, dissolve phosphoric acid in acetone to prepare phosphating solution, the solid-liquid mass ratio of phosphating solution to iron powder is 1:4, stir at room temperature for 30 minutes to completely disperse the powder, place the mixture in an oven at 110℃ for 2 hours, and after baking, cool naturally to room temperature to obtain passivated carbonyl iron powder with a phosphate conversion film of uniform thickness on the surface;
[0054] Silica coating treatment: The stirring speed was kept constant at 400 r / min throughout the process;
[0055] Sodium silicate slurry preparation: Take 25% of the mass of passivated iron powder in deionized water, dissolve sodium silicate pentahydrate to prepare a sodium silicate solution with a mass fraction of 8%, add the passivated iron powder and stir continuously to obtain slurry A;
[0056] Preparation of hydrochloric acid acidification solution: Take 5% of the mass of passivated iron powder with deionized water, dilute with 37% concentrated hydrochloric acid, and prepare hydrochloric acid solution B with a mass fraction of 9.1%.
[0057] Hydrolysis deposition reaction: Hydrochloric acid solution B is added dropwise to slurry A at a uniform rate for a total dropping time of 90 min; the dropping rate is adjusted in real time to control the pH at the reaction endpoint to 8.0; after the dropping is completed, the mixture is stirred at room temperature for 30 min to form a dense and continuous silica coating layer on the surface of the phosphate film.
[0058] Solid-liquid separation and washing: The slurry is vacuum filtered to obtain a filter cake, which is then washed three times with 5 times the weight of deionized water (based on the iron powder) until the conductivity of the filtrate is <50μS / cm, thus removing soluble salt impurities.
[0059] Inert atmosphere dehydration and drying: The water-washed filter cake is placed in a nitrogen-protected drying oven with a nitrogen flow rate of 0.5 L / min and a drying temperature of 100℃ for 4 hours to fully remove the free moisture from the powder.
[0060] Crushing, grading and sieving: The dried agglomerated powder is lightly dispersed by an air jet mill, batched in a three-dimensional mixer for 30 minutes, and then passed through a 200-mesh standard sieve to obtain the finished product of double-layer composite insulating carbonyl iron powder with D50=8.0μm.
[0061] Example 3 (Parameters for each process are taken at the upper limit of the range)
[0062] A composite insulation treatment process for carbonyl iron powder includes the following steps:
[0063] Phosphating and passivation treatment: Take carbonyl iron powder raw powder, add 1.0% of phosphoric acid by mass of raw powder, dissolve phosphoric acid in acetone to prepare phosphating solution, and the solid-liquid mass ratio of phosphating solution to iron powder is 1:4; stir at room temperature for 30 minutes to completely disperse the powder; place the mixture in an oven at 140℃ for 2 hours and bake at a constant temperature. After baking, cool naturally to room temperature to obtain passivated carbonyl iron powder with a thick phosphate conversion film on the surface.
[0064] Silica coating treatment: The stirring speed was kept constant at 400 r / min throughout the process;
[0065] Sodium silicate slurry preparation: Take 30% by weight of deionized water of passivated iron powder, dissolve sodium silicate pentahydrate to prepare a sodium silicate solution with a mass fraction of 10%, add the passivated iron powder and stir continuously to obtain slurry A;
[0066] Preparation of hydrochloric acid acidification solution: Take 6% by weight of deionized water from the passivated iron powder, dilute with 37% concentrated hydrochloric acid, and prepare a 10.5% hydrochloric acid solution B.
[0067] Hydrolysis deposition reaction: Hydrochloric acid solution B is added dropwise to slurry A at a uniform rate for a total dropping time of 100 min; the dropping rate is adjusted in real time to control the pH at the reaction endpoint to 8.3; after the dropping is completed, the mixture is stirred continuously at room temperature for 30 min to allow the silica colloid to fully deposit on the surface of the thick phosphate film to form a silica coating layer.
[0068] Solid-liquid separation and washing: The slurry is vacuum filtered to obtain a filter cake, which is then washed three times with 5 times the weight of deionized water (based on the iron powder) until the conductivity of the filtrate is <50μS / cm, thus removing soluble salt impurities.
[0069] Inert atmosphere dehydration and drying: The washed filter cake is placed in a nitrogen-protected oven with a nitrogen flow rate of 0.5 L / min and a drying temperature of 110℃. It is dried at a constant temperature for 4 hours. The drying temperature is then increased to fully remove the adsorbed moisture inside the thick phosphate film.
[0070] Crushing, grading and sieving: The dried agglomerated powder is lightly dispersed by an air jet mill, batched in a three-dimensional mixer for 30 minutes, and then passed through a 200-mesh standard sieve to obtain the finished product of double-layer composite insulating carbonyl iron powder with D50=8.2μm.
[0071] Comparative example (no phosphating pretreatment, single silica coating process)
[0072] Silica coating treatment: Carbonyl iron powder that has not undergone phosphating treatment is used directly, and the stirring speed is kept constant at 400 r / min throughout the process;
[0073] Sodium silicate slurry preparation: Take 25% of the iron powder by weight of deionized water, dissolve sodium silicate pentahydrate to prepare a sodium silicate solution with a mass fraction of 8%, and stir continuously to obtain slurry A;
[0074] Preparation of hydrochloric acid acidification solution: Take 5% of the iron powder mass of deionized water, dilute with 37% concentrated hydrochloric acid, and prepare hydrochloric acid solution B with a mass fraction of 9.1%;
[0075] Hydrolysis and deposition reaction: Hydrochloric acid solution B is added dropwise to slurry A at a uniform rate for a total dropping time of 90 min; the dropping rate is adjusted in real time to control the pH at the reaction endpoint to 8.0; after the dropping is completed, the mixture is stirred at room temperature for 30 min.
[0076] Solid-liquid separation and washing: The slurry was vacuum filtered to obtain a filter cake, which was washed three times with five times the weight of deionized water (5 times the weight of iron powder) until the conductivity of the filtrate was <50 μS / cm, removing soluble salt impurities. All coating parameters were completely consistent with the median values in Example 2, except for the lack of a phosphating pretreatment step and an inner phosphate conversion membrane.
[0077] Inert atmosphere dehydration and drying: The water-washed filter cake is placed in a nitrogen-protected oven with a nitrogen flow rate of 0.5 L / min and a drying temperature of 100℃ for 4 hours.
[0078] Crushing, grading and sieving: The dried agglomerated powder is lightly dispersed by an air jet mill, batched in a three-dimensional mixer for 30 minutes, and then passed through a 200-mesh standard sieve to obtain a finished product of carbonyl iron powder with single silica coating and D50=7.9μm.
[0079] Test: The powders and epoxy resins of each embodiment and comparative example were mixed evenly at a mass ratio of 92:8. This ratio is a common standard ratio in the one-piece molded inductor industry: 92wt% powder ensures that the magnetic ring has high saturation magnetic induction intensity and high magnetic permeability, while 8wt% epoxy resin serves as a binder phase, ensuring insulation between powder particles and giving the magnetic ring sufficient mechanical strength, thus balancing magnetic properties, insulation performance, and molding processability. If the amount of epoxy resin added is less than 8%, insufficient binder will easily lead to cracking of the magnetic ring and loose molding; if the amount added is more than 8%, it will significantly reduce the magnetic powder filling rate and the effective magnetic permeability will decrease significantly. Based on the comprehensive analysis, 92:8 is determined to be the optimal ratio for comparative testing.
[0080] After the mixture is thoroughly mixed using a dry mixing method, it is molded into a standard magnetic ring with an outer diameter of 10mm, an inner diameter of 6mm, and a thickness of 3mm. The ring is then cured at 120℃ for 1 hour. After cooling, performance tests are conducted. The corresponding instruments, standards, and operating procedures for each test are as follows:
[0081] Test method for surface insulation resistance of particles: powder four-probe method; test equipment: ZC-36 ultra-high resistance tester; referring to GB / T1410-2006 "Test methods for volume resistivity and surface resistivity of solid insulating materials", the dry powder is uniformly pressed into standard thin sheets, and the volume insulation resistance of the powder is determined by the four-probe electrode method, with the unit being MΩ·cm.
[0082] Eddy current loss (100mT magnetic flux density) at 1MHz was measured using a MAT-2000 high-frequency magnetic loss analyzer, in accordance with GB / T9632-2019 "Soft Magnetic Metal Powder Core". The test frequency was 1MHz, the alternating magnetic flux density was 100mT, and the ambient temperature was 25℃. The core loss per unit volume was recorded, with the unit being mW / cm³.
[0083] The dielectric breakdown voltage is determined using a withstand voltage breakdown tester, following the GB / T1408.1-2006 standard "Test Methods for Electrical Strength of Insulating Materials". The powder is cold-pressed into an unbonded sheet, and the pressure is increased at a uniform rate until the sample breaks down. The breakdown voltage value is then recorded.
[0084] The effective permeability μe (1MHz) was obtained by using an LCR digital bridge and testing the magnetic ring inductance according to GB / T38244-2019 "Test Method for Effective Permeability of Metal Powder Core". The effective permeability μe at 1MHz was then calculated.
[0085] The 85℃ / 85%RH damp heat aging test was conducted using a constant temperature and humidity aging test chamber, following GB / T2423.3-2016 "Environmental Testing Part 2: Test Methods Test Cab: Constant Damp Heat". The temperature was set at 85℃ and the relative humidity at 85%, and the aging was carried out continuously for 200 hours. After the aging was completed, the insulation resistance of the powder was re-measured, and the retention rate was calculated according to the formula: Insulation resistance retention rate = Insulation resistance after aging ÷ Insulation resistance before aging × 100%.
[0086] The average thickness of the coating layer (TEM characterization) was observed using transmission electron microscopy (TEM) to examine the microstructure of the powder. The sample preparation method was as follows: the powder was ultrasonically dispersed in anhydrous ethanol, and after the film was dropped and dried, it was observed on the TEM. The thickness of the inner phosphate layer and the outer silica layer were measured separately, and the fluctuation range of the film thickness was statistically analyzed.
[0087] Testing items Test conditions Comparative Example 1 Example 1 Example 2 Example 3 Surface insulation resistance of particles Powder Four-Probe Method 0.82 MΩ·cm 1.46 MΩ·cm 2.73 MΩ·cm 2.41 MΩ·cm 1MHz eddy current loss 100mT 425mW / cm³ 312mW / cm³ 186mW / cm³ 214mW / cm³ Dielectric breakdown voltage Powder tableting 126V 178V 265V 239V Effective permeability μe 1MHz 22.6 21.9 21.3 19.7 Insulation resistance retention rate after aging at 85℃ / 85%RH for 200 hours - 62.3% 78.5% 91.2% 86.7% Average thickness of the coating layer (TEM) - Uneven silicon layer, locally ranging from 120 to 420 nm. The phosphate layer is 25 nm thick, and the silicon layer is 80–110 nm thick. Phosphate layer 35nm, silicon layer 90-105nm Phosphate layer 60nm, silicon layer 100-130nm
[0088] Results analysis:
[0089] Insulation and eddy current loss: All process parameters in Examples 1 to 3 fall within the range defined in the claims. The insulation resistance and dielectric breakdown voltage of the double-layer composite insulation structure are significantly higher than those of the unphosphated Comparative Example 1, and the eddy current loss is greatly reduced.
[0090] Example 2 uses the middle ratio of the range, the thickness of the phosphating film and the silicon dioxide layer are matched evenly, the coating has no local accumulation or bottom leakage defects, the insulation performance is optimal and the high frequency loss is the lowest.
[0091] The magnetic properties change as the amount of phosphoric acid added and the baking temperature increase from the lower limit to the upper limit of the range, the thickness of the phosphate passivation film increases synchronously, the proportion of magnetic phase in the powder decreases, and the effective magnetic permeability gradually decreases. Example 2 achieves the optimal balance between high insulation performance and high magnetic permeability.
[0092] Moist heat aging resistance: The inner phosphate passivation film plays a role in corrosion inhibition and isolation of the iron substrate, while the outer silica layer blocks the penetration of water vapor and corrosive media. The insulation retention rate after damp heat aging of the double-layer synergistic protection structure is much better than that of single-layer silica-coated powder, resulting in stronger long-term working stability of inductor devices.
[0093] Microscopic coating morphology: Comparative Example 1 lacks a phosphate homogenization substrate, and the silica coating layer has local agglomeration and protrusions, and the particles have exposed defects. Examples 1 to 3 rely on the phosphate layer to homogenize the active sites on the particle surface, and the silica film is continuous and complete with a narrow thickness fluctuation range and no pores or bottom leakage defects.
Claims
1. A composite insulation treatment process for carbonyl iron powder, characterized in that: Includes the following steps: Step 1, passivation treatment: Dissolve phosphoric acid in an organic solvent. The weight of phosphoric acid is 0.3% to 1.0% of the weight of the carbonyl iron powder. Add the carbonyl iron powder and stir to mix evenly. Then bake the mixture to form a phosphate conversion film on the surface of the carbonyl iron powder, thus obtaining the passivated carbonyl iron powder. Step 2, silica coating: Dissolve sodium silicate in water to prepare a sodium silicate solution with a mass percentage of 6% to 10%, add the passivated carbonyl iron powder obtained in Step 1 and stir evenly to obtain part A; Concentrated hydrochloric acid was dissolved in water to prepare a hydrochloric acid solution with an HCl concentration of 7% to 11%, thus obtaining part B; Under the stirring conditions of part A, part B is added to part A at a uniform rate. Under the preset reaction conditions, the silica colloid formed by the hydrolysis and condensation of sodium silicate is deposited and coated on the surface of carbonyl iron powder particles with phosphate conversion film to form a silica coating layer. Then, it is filtered and washed with water. Step 3, Dehydration and Drying: The product obtained in Step 2 is dried and dehydrated under an inert atmosphere; Step 4: Crushing and sieving: The dried material obtained in Step 3 is crushed, batched, and sieved to obtain carbonyl iron powder with a double-layer composite insulating structure with a phosphate conversion film layer and a silica coating layer on the surface.
2. The composite insulation treatment process for carbonyl iron powder according to claim 1, characterized in that: The organic solvent in step one is acetone, and the baking temperature in step one is 80℃~150℃.
3. The composite insulation treatment process for carbonyl iron powder according to claim 1, characterized in that: The sodium silicate in step two is sodium silicate pentahydrate or sodium silicate nonahydrate, and the mass of the solvent water in the sodium silicate solution is 20% to 30% of the mass of the carbonyl iron powder after passivation treatment.
4. The composite insulation treatment process for carbonyl iron powder according to claim 1, characterized in that: In step two, the mass of the water solvent in the hydrochloric acid solution is 4% to 6% of the mass of the carbonyl iron powder after passivation treatment, and the concentrated hydrochloric acid is analytical grade concentrated hydrochloric acid with an HCl mass concentration of 37%.
5. The composite insulation treatment process for carbonyl iron powder according to claim 1, characterized in that: In step two, the time for uniformly adding part B to part A is 30 to 120 minutes. The preset reaction conditions are that the pH is controlled between 7 and 8.
5. After the addition is completed, continue stirring for 20 to 40 minutes.
6. The composite insulation treatment process for carbonyl iron powder according to claim 1, characterized in that: The inert atmosphere in step three is nitrogen atmosphere, and the drying temperature is 80℃~120℃.
7. The composite insulation treatment process for carbonyl iron powder according to claim 1, characterized in that: The particle size D50 of the carbonyl iron powder product obtained in step four is 3μm to 50μm.
8. The composite insulation treatment process for carbonyl iron powder according to claim 1, characterized in that: In step two, the filtered product is washed with deionized water at least three times to remove residual soluble salts from the surface.
